Circulating exosomes decrease in size and increase in number between birth and age 7: relations to fetal growth and liver fat - Díaz, Marta; Casano, Paula; Quesada, Tania; López-Bermejo, Abel; de Zegher, Francis; Villarroya, Francesc; Ibáñez, Lourdes (Frontiers in Endocrinology, 2023)
Exosomes play a key role in cell-to-cell communication by transferring their cargo to target tissues. Little is known on the course of exosome size and number in infants and children.Methods: Longitudinally, we assessed the size and number of circulating exosomes at birth and at ages 2 and 7 yr in 75 infants/children born appropriate-for-gestational-age (AGA; n=40) or small-forgestational-age (SGA; n=35 with spontaneous catch-up), and related those results to concomitantly assessed measures of endocrine-metabolic health (HOMA-IR; IGF-1), body composition (by DXA at ages 0 and 2) and abdominal fat partitioning (subcutaneous, visceral and hepatic fat by MRI at age 7).Results: Circulating exosomes of AGAs decreased in size (on average by 4.2%) and increased in number (on average by 77%) between birth and age 7. Circulating exosomes of SGAs (as compared to those of AGAs) had a larger size at birth [146.8 vs 137.8 nm, respectively; p=0.02], and were in lower number at ages 2 [4.3x10 11 vs 5.6x10 11 particles/mL, respectively; p=0.01] and 7 [6.3x10 11 vs 6.8x10 11 particles/mL, respectively; p=0.006]. Longitudinal changes were thus more pronounced in SGAs for exosome size, and in AGAs for exosome number. At age 7, exosome size associated (P<0.0001) to liver fat in the whole study population.Early-life changes in circulating exosomes include a minor decrease in size and a major increase in number, and these changes may be influenced by fetal growth. Exosome size may become one of the first circulating markers of liver fat in childhood.